2014
DOI: 10.3389/fphys.2014.00413
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid induces integrin activation in vascular smooth muscle and alters arteriolar myogenic vasoconstriction

Abstract: In vascular smooth muscle cells (VSMC) increased integrin adhesion to extracellular matrix (ECM) proteins, as well as the production of reactive oxygen species (ROS) are strongly stimulated by lysophosphatidic acid (LPA). We hypothesized that LPA-induced generation of ROS increases integrin adhesion to the ECM. Using atomic force microscopy (AFM) we determined the effects of LPA on integrin adhesion to fibronectin (FN) in VSMC isolated from rat (Sprague–Dawley) skeletal muscle arterioles. In VSMC, exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 65 publications
2
21
0
Order By: Relevance
“…Prior studies have shown that activation of integrins with histamine, LPA or divalent metal ions induces a stronger interaction of FN with integrins, which can be ruled out in the current studies as such activators were not used and our experiments were performed under identical conditions for the native and glycated proteins. For our studies, in addition to integrins, we focused on RAGE as likely candidate receptor for AGEs as the literature supports RAGE being the predominant cell surface receptor on VSMC that interacts with glycated proteins …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Prior studies have shown that activation of integrins with histamine, LPA or divalent metal ions induces a stronger interaction of FN with integrins, which can be ruled out in the current studies as such activators were not used and our experiments were performed under identical conditions for the native and glycated proteins. For our studies, in addition to integrins, we focused on RAGE as likely candidate receptor for AGEs as the literature supports RAGE being the predominant cell surface receptor on VSMC that interacts with glycated proteins …”
Section: Discussionmentioning
confidence: 98%
“…To determine binding specificity and the role for specific integrins in adhesive events between native and glycated proteins and the cell surface, passage 2 VSMC were serum starved for one hour and then incubated with 30 μg/mL of anti‐α5 integrin monoclonal antibody (HMα5‐1), anti‐β1 integrin monoclonal antibody (Ha2/5), anti‐β3 integrin monoclonal antibody (F11), or isotype control antibodies for 45 minutes before performing AFM experiments. Antibodies were purchased from BD Pharmingen (San Jose, CA) as previous studies in our laboratory, and others have used these antibodies to specifically block the interaction between α5, β1, and β3 integrins with their ligands . To determine the role of RAGE in adhesion of glycated protein to VSMC, we performed similar AFM experiments but incubated the cells with a RAGE inhibitor 50 nM FPS‐ZM1 (EMD Millipore, Billerica, MA) or 0.02% control vehicle DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…Although this is the first definitive study of the mechanism for generation of LPA, several studies have suggested the involvement of LPA signaling in NOX2 activation. For example, LPA treatment increased superoxide generation in eosinophils (59), PMNs (60), and endothelial cells (42), as well as rac1‐dependent and gp91dstat‐sensitive oxidant generation in smooth muscle cells (61, 62). Further, the NOX2 cytoplasmic factor p47 phox has been shown to colocalize with a LPAR1 during NOX2 activation (63).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LPA is associated with vascular pathology and is known to exert multiple harmful effects on vascular endothelial (Rizza et al ., ; Panetti et al ., ; van Nieuw Amerongen et al ., ; Panetti, ; Panetti et al ., ; Lin et al ., ; Avraamides et al ., ; Lin et al ., ) and smooth muscle (Hayashi et al ., ; Panchatcharam et al ., ) integrity. In particular, studies have shown that LPA can lead to increased levels of ROS either independent of (Brault et al ., ; Staiculescu et al ., ) or in conjunction with decreased eNOS expression (Chen et al ., ), effectively decreasing endothelium‐dependent dilation to bradykinin in porcine arterioles (Chen et al ., ). We extend these findings and demonstrate that acutely elevated levels of LPA disrupt endothelium‐dependent FID in human arterioles by shifting the mechanism away from NO to mtH 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%